Factors Associated With Remote Diffusion-Weighted Imaging Lesions in Spontaneous Intracerebral Hemorrhage - Ye, Xiang-hua; Gao, Ting; Xu, Xu-hua; Cai, Jin-song; Li, Jia-wen; Liu, Kai-ming; Song, Shui-jiang; Yin, Xin-zhen; Tong, Lu-sha; Gao, Feng (Frontiers in Neurology, 2018)
Background and purpose: Remote diffusion-weighted imaging lesions (R-DWILs) have been detected in patients with spontaneous intracerebral hemorrhage (ICH), and may be correlated with clinical outcome. However, the mechanisms and characteristics of R-DWILs have not been fully elucidated. In this study, we sought to demonstrate the clinical characteristics of R-DWILs in spontaneous ICH. Methods: We prospectively collected data with spontaneous ICH patients from November 2016 to December 2017. In these patients, cerebral magnetic resonance imaging (MRI) was performed within 28 days after ICH onset. R-DWIL was defined as a hyperintensity signal in DWI with corresponding hypointensity in apparent diffusion coefficient (ADC), and at least 20 mm apart from the hematoma. We compared two groups of patients with or without R-DWIL with the demographic and clinical characteristics, laboratory parameters and imaging characteristics, by using univariate and multivariate analysis. Results: Of the 222 patients enrolled, a total of 75 R-DWILs were observed in 41 patients (18.5%). Among these lesions, the cortical and subcortical areas were the predominant locations with a proportion of 77.3%. The median diameter of R-DWILs was 7 mm (range 2-20 mm). Twelve patients were found having more than one lesion, with 5 among which showed R-DWILs in multiple cerebral arterial territories. In multivariate modeling, higher fasting glucose (OR 1.231; 95% CI 1.035-1.465; p=0.019) and more severe white matter hyperintensity (WMH) (OR 6.589; 95% CI 2.975-14.592; p<0.001) were independent factors related to the presence of R-DWILs. Conclusions: In our study, approximately one fifth of ICH patients showed coexistence of R-DWIL. Higher fasting glucose and more severe WMH were associated with R-DWIL occurrence in spontaneous ICH.